Peningkatan Estetika Kawasan Kampung Ketupat Samarinda Melalui Desain Sculpture: Improving the Aesthetics of Kampung Ketupat Samarinda Through Sculpture Design - Hidayati, Zakiah; Putra, Hatta Musthafa Adham; Fahrezi, Irgi Ahmad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Kampung Ketupat, located in the District of Samarinda Seberang - Samarinda, has been a tourist destination since 2017. Kampung Ketupat is one of the old villages in Samarinda located along the Mahakam River, consisting of stilt houses made from ironwood. Many of its residents are artisans who make 'ketupat' (woven palm leaf pouches for rice) containers sold in Samarinda and the surrounding areas. As time passes, facilities such as sculptures in Kampung Ketupat gradually become obsolete both in terms of appearance and materials. Based on these problems, the Building Architecture Study Program - Samarinda State Polytechnic, through Community Service activities, provided a solution to the problem with the Kampung Ketupat sculpture design approach, which is more in line with the needs of the tourist area. The implementation method is direct observation in the field, the study of related literature, interviews with local community groups and communities, and design activities. The result of the activity is a complete working drawing that can be used as a reference in making new sculptures by the management of Kampung Ketupat. Apart from the sculpture's proportions being more monumental, the update includes a more modern and Instagrammable design form and lighting on several sides. The working drawings can be an important input for plans to improve the aesthetics of the Kampung Ketupat area.